Vaccination of Сhildren in the Kyrgyz Republic - Gulzhan S. Kitarova; T. T. Mamyrbaeva; A. Suvanbekov; V. K. Shukurova (Педиатрическая фармакология)
Vaccination is concidered worldwide as the most effective preventive measure for many pediatric infectious diseases (vaccine-controlled).Objective. The goal of the study was to assess the current state of immunization and parent awareness on the vaccination of children under the age of five.Methods: Analysis of data reported by the National Reporting System on the state of vaccination of children under age of five as well as analysis of two representative multi-indicator cluster and medico-demographic studies were used in the study. Cluster study of mothers’ general awareness and their attitude towards vaccination of children under the age of five was conducted. Total of 30 clusters from 93 villages in the region were selected by random sampling.Results: In the Kyrgyz Republic, the coverage rates of children with a full range of vaccinations in accordance with the National Vaccination Schedule based on reported official statistics and two representative household-level studies are contradictory and range from 72.5% to 97.5%. In the last 15 years, the proportion of children aged 18–29 months who received all main vaccines recommended by WHO decreased by 10% points. The status of vaccinating children was influenced by the level of mothers’ awareness on the importance of vaccination: 34.4% of respondents denied vaccinations due to disbelief of the possibility of preventing infectious diseases by vaccination, versus 4.2% of mothers who doubted the effectiveness of vaccinations. Meanwhile, the quality of counseling to mothers performed by health professionals does not contribute to a better understanding of the importance of vaccination for children’s health and survival.Conclusion. The results of the study indicate the vaccination coverage reduction, unreliability of registered number of vaccinated children, and low level of informational awareness on the importance of vaccination for the prevention of a number of infectious diseases and improvement the survival rate in children under 5 years. This data should be considered when developing programs for the improvement of coverage levels for vaccinations in in the Kyrgyz Republic.